Pemberian Insentif Pajak Penghasilan di Bidang Penanaman Modal dalam Perspektif Teori Hukum - Batara Mulia Hasibuan (Nagari Law Review, 2019)
Tax has an important role in the governance of the state, including Indonesia which relies on tax revenues, to accelerate the creation of public welfare and the achievement of state objectives, as stated in the Preamble of the 1945 Constitution. Article 23 A The 1945 Constitution clearly determines taxes and other levies are regulated by law. The very foundation of this constitution must be interpreted legally that tax collection must be based on sound legal principles. The principle of the tax law must be based on fairness and equity in carrying the tax burden in accordance with the ability of the people. To increas the collecting of tax, the government applies policy such as through the provision of tax incentive facilities. This tax incentive is expected to be a concern for investors to make investments in Indonesia. The provision of tax incentive facilities in the context of investment needs to be reviewed in the perspective of legal theory, especially in terms of justice and its usefulness in the development of investment and the achievement of people's welfare. The method in this study uses the normative juridical method, using the statutory approach. The provision of income tax incentives in the investment sector is an embodiment of investment facilities, which is one of the factors that influence the growth and interest of foreign investors in investment in Indonesia. In the perspective of legal theory, the provision of this income tax incentive, which is regulated in the law, both the Income Tax Act and the Investment Act, which was formed by the authorized body for that, especially from the theory of utilitarianism and positive legal order must be guided by hierarchically in grundnorm (basic norm).